(untitled) (International Journal of Automation and Smart Technology, 2020)
Fused Deposition Modelling (FDM) is one of the widely utilized technology of low-cost 3D Printing. It uses plastic filament as material for Additive Manufacturing. To lessen the amount of filament consumption of the prints, modification of the infill patterns was conducted. This study focuses on the introduction of new infill pattern – the lattice infill to increase material efficiency of 3D prints, compared to conventional infill patterns. Benchmark designs such as the grid and cubic infill pattern were first created by the 3D printer slicing software. The proposed lattice infill design was created using a CAD software and rendered as STL file for compatibility with the slicing software. The three infill patterns were simulated in the slicing software to measure approximate product weight and the proposed design is simulated in an engineering simulation software to determine the stress performance and displacement when an external force is introduced. Results showed that the new infill pattern saves material up to 61.3% compared to conventional infill patterns. In effect, it increased the amount of prints produced per spool by 2.5 times. It is also found out that the lattice infill pattern print can resist to up to 1.6kN of compressive load prior to breaking.